Modeling and simulation of extended ant colony labor division for benefit distribution of the all-for-one tourism supply chain with front and back decoupling - Liao, Rundong; Li, Shufang; Wu, Conghui; Zhang, Xiang; Jiang, Changbing; Li, Ruolan (Frontiers in Bioengineering and Biotechnology, 2023)
This paper takes the supply chain alliance under the decoupling of the front and back of the all-for-one tourism as the research object. Considering the three behavior stimuli of self-benefit, altruism and invariance, this article resets the attributes such as environmental stimuli and response threshold of ants based on the characteristics of the all-for-one tourism supply chain with shared services as the core under the decoupling of the front and back. Moreover, it introduces dual intervention factors to coordinate the benefit distribution process of different member companies, takes fairness as the main goal of benefit distribution, and introduces relative deprivation as the measure index of fairness, and establishes a dynamic all-for-one tourism supply chain alliance benefit distribution model. Experimental results show that the extended model has good flexibility of benefit distribution and realizes the fair distribution of supply chain benefits.